1985
DOI: 10.2135/cropsci1985.0011183x002500060039x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships Among Hard Red Winter Wheat Cultivars as Evaluated by Pedigree Analysis and Gliadin Polyacrylamide Gel Electrophoretic Patterns1

Abstract: Genetic relationships for all 903 pairwise combinations of 43 hard red winter wheat cultivars were evaluated using two indices: coefficient of parentage (r), computed from pedigree analysis, and a similarity coefficient (s), based on gliadin polyacrylamide gel electrophoresis (PAGE) patterns. Each index may vary from 0 for two unrelated cultivars to 1 for two identical cultivars. Mean r and s over all cultivars were 0.24 and 0.55, respectively. Cluster analyses based on the r and s matrices revealed dissimilar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 0 publications
1
43
0
2
Order By: Relevance
“…Selection of parents for hybridization (Frei et al, 1986) and the progeny performance prediction (Hallauer and Miranda, 1988) alleviates on the availability of information about genetic relationships among accessions within the species. Variations in the environmental conditions have a great impact on the accuracy of the data gathered from the parental information, morphological characters, and isozyme studies (Autrique et al, 1996;Cox et al, 1985;Shamsuddin, 1985). For this problem, a substantial answer has emerged in the form of molecular markers that can be presented as a potential tool for evaluating genetic variability among the intimately linked cultivars of wheat varieties (Davila et al, 1998;Kim and Ward, 1997;Plaschke et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Selection of parents for hybridization (Frei et al, 1986) and the progeny performance prediction (Hallauer and Miranda, 1988) alleviates on the availability of information about genetic relationships among accessions within the species. Variations in the environmental conditions have a great impact on the accuracy of the data gathered from the parental information, morphological characters, and isozyme studies (Autrique et al, 1996;Cox et al, 1985;Shamsuddin, 1985). For this problem, a substantial answer has emerged in the form of molecular markers that can be presented as a potential tool for evaluating genetic variability among the intimately linked cultivars of wheat varieties (Davila et al, 1998;Kim and Ward, 1997;Plaschke et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity has been evaluated in wheat and its relatives using morphological data (Lee & Kaltsikes, 1973), protein variation (Cox et al, 1985;Graybosch, 1992) and DNA markers (Chen et al, 1994;Barrett et al, 1998;Paull et al, 1998;Bohn et al, 1999;Prasad et al, 2000;Soleimani et al, 2002;Almanza-Pinzon et al, 2003;Naghavi et al, 2004Naghavi et al, , 2007. However, it is important to determine whether different diversity estimation methods provide similar information concerning the degree of variation among wheat genotypes (Burkhamer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, we know that the studied cultivars are the result of both natural and human selection. However, Cox et al (1985) found a low but significant correlation coefficient between genetic relationship based on coefficient of parentage and genetic relationship based on gliadin PAGE patterns.…”
Section: Introductionmentioning
confidence: 79%
“…This region was originally a non-carrier area, but after the import of consumption (Ne2) wheat grains from Eastern Europe since the 14th century (Zeven, 1980(Zeven, , 1986 and the use of this imported material as sowing seed, it also became an Ne2-area. Cox et al (1985) identified major and minor ancestors of 43 US HRW wheat cultivars. The major ancestors are the HRW Turkey, the SRW cultivars Kawvale and Mediterranean, the HRS cultivars Red Fife, Hard Red Calcutta and Kenya 58, and the SRS Purplestraw.…”
Section: Introductionmentioning
confidence: 99%